Profil penderita Diabetes Mellitus Tipe-2 (DM-2) dengan komplikasi yang menjalani rawat inap di Rumah Sakit Umum Daerah (RSUD) Klungkung, Bali tahun 2018 - I Gede Restu Mahendra Sugiarta; I Gusti Ketut Darmita (Intisari Sains Medis, 2020)
Background: DM is a metabolic disease with the characteristic of hyperglycemia due to insulin abnormality, insulin action, or a combination of insulin abnormality and insulin action. Klungkung accounted for the third-largest prevalence of DM after Jembrana and Buleleng with 1.6%. Preliminary survey in Klungkung’s Hospital 2019, shown that the number of patients with T2DM with a complication that hospitalized in 2018 were 253 people.Method: This was a cross-sectional descriptive study aimed to determine the proportion of T2DM patient with complication and average Length of Stay (LOS) T2DM patient with complication. This study was carried out at the medical record installation of Klungkung’s Hospital using secondary data obtained from medical record Klungkung’s Hospital. Samples were all T2DM patients with the complication that hospitalized with 253 samples using a total sampling method. Data were processed and analyzed using the SPSS version 21 for Windows.Result: The highest proportion of T2DM patient with complication based on age was 61 to 70 years old (36.0%), based on sex was men (54.5%), based on complication was diabetic foot (18.2%), based on treatment was insulin (83.4%), based on discharged from hospital was outpatient treatment (90.5%), and based on source of cost was BPJS (94.9%). The average LOS for patients T2DM with complication was 5.81 day.Conclusion: Effort needed to reduce the prevalence of T2DM with complication and needed maximum services in the management of T2DM with complication to prevent further worsening patient’s condition of T2DM with complication. One of them is giving strong education to patient regarding T2DM with complication. Latar Belakang: DM merupakan penyakit metabolik dengan karakteristik berupa hiperglikemia akibat kelainan insulin, kerja insulin, atau kombinasi dari kelainan insulin dan kerja insulin. Klungkung menyumbang prevalensi DM terbesar ketiga setelah Jembrana dan Buleleng sebesar 1,6%. Survei pendahuluan di RSUD Klungkung 2019, mendapatkan jumlah penderita DMT2 beserta komplikasi yang dirawat inap tahun 2018 sebanyak 253 orang.Metode :. Penelitian ini merupakan penelitian deskriptif cross sectional untuk mengetahui proporsi penderita DMT2 dengan komplikasi dan lama rawatan rata-rata penderita DMT2 dengan komplikasi. Penelitian dilaksanakan di instalasi rekam medis RSUD Klungkung menggunakan data sekunder yang diperoleh dari catatan rekam medis di RSUD Klungkung. Sampel adalah semua penderita DMT2 dengan komplikasi yang dirawat inap dengan jumlah 253 orang menggunakan metode total sampling. Data diolah dan dianalisis menggunakan program SPSS versi 21 untuk Windows.Hasil : Proporsi penderita DMT2 dengan komplikasi tertinggi pada umur 61 s/d 70 tahun (36,0%), jenis kelamin pada laki-laki (54,5%), komplikasi pada diabetic foot (18,2%), pengobatan pada insulin (83,4%), keadaan sewaktu pulang pada berobat jalan (90,5%), dan sumber biaya pada BPJS (94,9%). Lama rawatan rata-rata penderita DMT2 dengan komplikasi adalah 5,81 hari.Kesimpulan: Diperlukan suatu upaya untuk menurunkan angka kejadian DMT2 dengan komplikasi serta memaksimalkan pelayanan dalam penatalaksanaan DMT2 dengan komplikasi untuk mencegah perburukan komplikasi penderita yang lebih lanjut. Salah satunya berupa pemberian edukasi yang kuat kepada penderita mengenai DMT2 beserta komplikasi.